The choroid plexus sodium‐bicarbonate cotransporter NBCe2 regulates mouse cerebrospinal fluid pH. (12th August 2018) - Christensen, Henriette L.; Barbuskaite, Dagne; Rojek, Aleksandra; Malte, Hans; Christensen, Inga B.; Füchtbauer, Annette C.; Füchtbauer, Ernst‐Martin; Wang, Tobias; Praetorius, Jeppe; Damkier, Helle H.
Abstract : Key points: Normal pH is crucial for proper functioning of the brain, and disorders increasing the level of CO2 in the blood lead to a decrease in brain pH. CO2 can easily cross the barriers of the brain and will activate chemoreceptors leading to an increased exhalation of CO2 . The low pH, however, is harmful and bases such as HCO3 − are imported across the brain barriers in order to normalize brain pH. We show that the HCO3 − transporter NBCe2 in the choroid plexus of the blood‐cerebrospinal fluid barrier is absolutely necessary for normalizing CSF pH during high levels of CO2 . This discovery represents a significant step in understanding the molecular mechanisms behind regulation of CSF pH during acid‐base disturbances, such as chronic lung disease. Abstract: The choroid plexus epithelium (CPE) is located in the brain ventricles where it produces the majority of the cerebrospinal fluid (CSF). The hypothesis that normal brain function is sustained by CPE‐mediated CSF pH regulation by extrusion of acid‐base equivalents was tested by determining the contribution of the electrogenic Na + ‐HCO3 − cotransporter NBCe2 to CSF pH regulation. A novel strain of NBCe2 ( Slc4a5 ) knockout (KO) mice was generated and validated. The base extrusion rate after intracellular alkalization was reduced by 77% in NBCe2 KO mouse CPE cells compared to control mice. NBCe2 KO mice and mice with CPE‐targeted NBCe2 siRNA knockdown displayed a reduction in CSF pH recovery during hypercapnia‐induced acidosis of approximately 85% and 90%, respectively, compared to control mice. NBCe2 KO did not affect baseline respiration rate or tidal volume, and the NBCe2 KO and wild‐type (WT) mice displayed similar ventilatory responses to 5% CO2 exposure. NBCe2 KO mice were not protected against pharmacological or heating‐induced seizure development. In conclusion, we establish the concept that the CPE is involved in the regulation of CSF pH by demonstrating that NBCe2 is necessary for proper CSF pH recovery after hypercapnia‐induced acidosis. Key points: Normal pH is crucial for proper functioning of the brain, and disorders increasing the level of CO2 in the blood lead to a decrease in brain pH. CO2 can easily cross the barriers of the brain and will activate chemoreceptors leading to an increased exhalation of CO2 . The low pH, however, is harmful and bases such as HCO3 − are imported across the brain barriers in order to normalize brain pH. We show that the HCO3 − transporter NBCe2 in the choroid plexus of the blood‐cerebrospinal fluid barrier is absolutely necessary for normalizing CSF pH during high levels of CO2 . This discovery represents a significant step in understanding the molecular mechanisms behind regulation of CSF pH during acid‐base disturbances, such as chronic lung disease.